2017
DOI: 10.1016/j.jadohealth.2017.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Sexting and the Definition Issue

Abstract: Sexting among youths has become a necessary topic of interest in research because of the negative consequences that this activity could create, especially when content is shared with others. Indeed, this loss of control could lead to humiliation, (cyber)bullying, or harassment. The development of new technologies, press coverage, and increase of prevalence rates could also explain the growth of interest in sexting. However, its definition is still a gray area. This review examines the different definitions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
135
1
19

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 184 publications
(162 citation statements)
references
References 38 publications
7
135
1
19
Order By: Relevance
“…Weekes-Shackelford (eds. ), Encyclopedia of Evolutionary Psychological Science, https://doi.org/10.1007/978-3-319-16999-6_218-1 (Barrense-Dias et al 2017;Englander 2015;Van Ouytsel et al 2017). Outside of a relationship context, sexting has also been found to occur as a joke, a dare, or as a bonding ritual between friends (Lippman and Campbell 2014;Van Ouytsel et al 2017).…”
Section: Motivesmentioning
confidence: 99%
See 2 more Smart Citations
“…Weekes-Shackelford (eds. ), Encyclopedia of Evolutionary Psychological Science, https://doi.org/10.1007/978-3-319-16999-6_218-1 (Barrense-Dias et al 2017;Englander 2015;Van Ouytsel et al 2017). Outside of a relationship context, sexting has also been found to occur as a joke, a dare, or as a bonding ritual between friends (Lippman and Campbell 2014;Van Ouytsel et al 2017).…”
Section: Motivesmentioning
confidence: 99%
“…Scholars have defined sexting in a variety of ways, from broad definitions that include the sending of all types of self-made sexually explicit media (Barrense-Dias et al 2017) to more specific definitions that are limited to sending photos and videos of particular body parts. Studies also differ in the timeframe; respondents were asked to recall (e.g., 6 months vs. a year), and whether the studies were conducted among adolescents or adults.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the sources of variability lies in the definition used [8]. When more restricting definitions are used, which only consider sexting to occur when there are sexually explicit or nude images, we find that approximately 5%-28% of adolescents admit to sexting [9], whereas when broader definitions are used, which also recognize suggestive images, over 60% of young people admit to sexting [10].…”
Section: Introductionmentioning
confidence: 87%
“…There is no single, agreed‐upon definition for sexting. Recently Barrense‐Dias, Berchtold, Suris, and Akre () undertook a review of 223 articles related to teen (age 18 and under) sexual communication identified from academic databases using the search terms “sexting”, “sex‐texting”, “sexual messaging”, and “sexto” (Spanish for “sext”) to describe the behavior. Based on their inclusion criteria they utilized 18 studies to evaluate how researchers define sexting.…”
Section: Defining and Measuring Sextingmentioning
confidence: 99%